(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Korolskyy V. V., Kapinosov A. M. Mathematical conceptual competence: theoretical and methodological bases of research, structure and levels. The article presents theory-and-methodology bases of the investigation of conceptual competence as a type of mathematical competence, characterizes its stages, defines its structure and levels.